Optimizing sandwich foam floats for amphibious aircraft: enhancing performance under water impact - Djamaluddin, Fauzan; Ahmad, Zaini (Frontiers in Mechanical Engineering, 2025)
Improving amphibian aircraft landing performance is the primary goal of this paper, which aims to optimize the design of sandwich aluminum foam (SAF) energy absorbers. To determine how various configurations of the sandwich structure’s layers affected landing performance, extensive transient dynamic simulations were used. Using simulation methodologies, the impact performance of the SAF’s design parameters was rigorously investigated. The first step of the study was to characterize the SAF as a material for use in impact applications. The three SAF samples were subjected to testing in a water impact environment with a 3.5-ton airplane weight and a landing speed of 76 knots. The core thicknesses of the samples were 3 mm, 5 mm, and 7 mm, respectively. The numerical simulation findings showed that crash behavior indicators like peak crushing force (PCF) and total energy absorption (TEA) are greatly affected by core thickness and material density. Finite element model compares with experiment test, it is found that the differences less than 5%. These meshes are simulated to obtain convergent points of the simulated model mesh size with the error value is 3.08%. Surrogate models based on the Radial Basis Function (RBF) and the Non-dominated Sorting Genetic Algorithm II (NSGA-II) were used in a multi-objective optimization strategy to improve the float’s crashworthiness. According to the optimization findings, the SAF float was far more crashproof than the previous float design. These optimal results differ from those derived solely from crushing analyses in prior studies, providing a more robust reference for practical engineering applications.